Answer: 4x^2 - 10x - 6
Step-by-step explanation:
You can use FOIL to do this. First terms, Outer terms, Inner terms, Last terms.
(x - 3)(4x + 2)
First terms: x * 4x = 4x^2
Outer terms: x * 2 = 2x
Inner terms: -3 * 4x = -12x
Last terms: -3 * 2 = -6
Now add these together:
4x^2 + 2x - 12x - 6 = 4x^2 - 10x - 6
It’s 4 ik know this it’s four cixhdhdud didjdhdh djdjdhd djdjdhd
Answer:
5x - 63 = 6
Step-by-step explanation:
Okay, first step, let's get all fractions having a common denominator, to do this, multiply 2/3 by 3 to get 6/9. Now, we have 5/9x-7=6/9. To make these into whole numbers, we can multiply the whole equation by the denominator (9). 5/9x multiplied by 9 is 5. 7 multiplied by 9 is 63. 6/9 multiplied by 9 is 6. Now we have 5x-63=6. If I were to simplify the equation, it would require decimals, so I'll leave it at this, but the equation simplified is x=13.8.
It’s rather half of that or double of that
The expression can be represented as 16 3/4 divided by 3 7/8